AB0152 The rs11792633-t allele of il-33 gene is associated with systemic sclerosis. (23rd January 2014) - Koca, S. S.; Pehlivan, Y.; Kara, M.; Oner, F. A.; Yilmaz, N.; Cetin, G. Y.; Kisacik, B.; Ozgen, M.; Pamuk, O. N.; Direskeneli, H.; Sayarlioglu, M.; Onat, A. M.
Abstract : Background: Systemic sclerosis (SSc) is a chronic inflammatory disease characterized by widespread fibrosis of the skin and several visceral organs. Its pathogenesis is not fully known. However, T lymphocytes actives fibroblasts directly via CD154/CD40 ligand or indirectly via pro-fibrotic cytokines including interleukin (IL)-4, IL-6 and transforming growth factor (TGF)-β. Therefore, extracellular matrix components such as collagen and fibronectin are produced by active fibroblasts. The pro-fibrotic potential of IL-33 has been demonstrated by in both in vitro and in vivo settings; moreover, increased level of IL-33 has also been reported in patients with SSc. Objectives: The aim of the present study was to detect the potential association of IL-33 gene polymorphisms on the susceptibility of SSc. Methods: 300 SSc patients and 280 healthy controls (HC) from 6 different regions of Turkey were enrolled in this multicentric preliminary candidate gene study. DNA samples were harvested using an appropriate commercial DNA isolation kit. Four single nucleotide polymorphisms (SNPs) of IL-33 gene (rs7044343, rs1157505, rs11792633 and rs1929992) were genotyped using the appropriate commercial primer/probe sets on real-time PCR. Statistical analysis was performed by Chi-square test, and odds ratio (OR) and 95% confidence interval (CI) were determined for alleles. The Tukey-Kramer's method for multiple testing was used and P values less than 0.0125 were considered as significant. Results: There was no significant difference in terms of the genotypic distributions of evaluated four IL-33 polymorphisms between the SSc and HC groups (p>0.05 for all). Moreover, allelic distributions and MAF of rs7044343, rs1157505, and rs1929992 polymorphism were not significantly different (p>0.05 for all). However, the frequency of rs11792633-T allele was significantly higher in the SSc group compared to the HC group (0.0001, OR: 1.5, % 95 CI: 1.2-1.8). Conclusions: This preliminary candidate gene study demonstrates thatrs11792633-T allele of IL-33 gene is associated with the susceptibility to the SSc in Turkish population. It may be suggested that IL-33 gene may be a candidate gene to research in SSc. References: Schmitz J, et al. Immunity. 2005;23:479-90. Rankin AL, et al. J Immunol. 2010;184(3):1526-35. Manetti M, et al. Ann Rheum Dis. 2011;70(10):1876-8. Yanaba K, et al. Clin Rheumatol. 2011;30(6):825-30. Terras S, et al. Ann Rheum Dis. 2013;72(1):144-5. Acknowledgements: none Disclosure of Interest: None Declared